DIFFICULTES IN FIRST INCISORS ERUPTION CAUSED BY MESIODENS - Pisevska, Sofijanka Gerasimova; Arsovska, Mirjana Markovska; Gorovska, Maja Popovska; Chadikovska, Elizabeta (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
Supernumerary teeth are infrequent developmental anomaly that can appear in any area of the dental arch and can affect any dental organ.Hyperdontia is rare in population except if it is associated with other diseases or syndromes. Treatment of hyperdontia depends on the area where supernumerary teeth appear, their number and the presence of pathologic processes around the teeth.Mesiodens are the most common supernumerary teeth and the reason for their appearance is still not elucidated. Proliferation of dental lamina and genetic factors have been implicated.Mesiodens can cause delayed or ectopic eruption of the permanent incisors.Early diagnosis allows minimal invasive treatment, which may include surgical extraction.If permanent teeth do not erupt in a reasonable period after extraction, surgical exposure and orthodontic treatment may be required to ensure eruption and to create sufficient arch space before eruption and alignment of the incisor(s). Key words: Supernumerary teeth, developmental anomaly, orthodontic treatment